Adoption of climate-smart agriculture in the coastal area of Bangladesh (International Journal of Agricultural Research, Innovation and Technology, 2025)
Adopting climate-smart agriculture in the coastal area of Bangladesh faces challenges, as well as farmers' vulnerability to frequent natural disasters and salinity intrusion. The main aims of this study were to assess the extent of CSA technologies adopted by the farmers and to explore the contributions of the selected characteristics of the coastal farmers to the adoption of CSA. An interview schedule was used to collect data from 354 coastal farmers of three districts, namely Satkhira, Khulna, and Bagerhat, through a ‘Multistage random sampling method’ in 2022. Both inferential and descriptive statistics were used. A complete model multiple regression analysis was used to investigate how the predictor variables affected the outcome variables. Results indicate that about 57.91% of the coastal farmers had medium adoption, followed by 22.88% high and 19.21% poor adoption of CSA. Out of the 19 identified CSA technologies, “the use of thread pipe/plastic pipe for irrigation” ranked first and indicated the highest extent of adoption by the coastal farmers. Farmers’ annual agricultural income, extension contact, training exposure, knowledge of CSA, and attitude towards CSA significantly positively contributes to their adoption of CSA. Extension services, community-based training, and awareness campaigns can play a vital role in escalating farmers' adoption of CSA. Therefore, addressing climate change and building climate resilience in agriculture requires practical support to enable farmers to adopt and sustain CSA.Int. J. Agril. Res. Innov. Tech. 15(1): 39-47, June 2025